MUSLIMAH KARIER DALAM PANDANGAN ISLAM - Syofrianisda Syofrianisda (Jurnal Ulunnuha, 2019)
Women are half a part of a society. He is also a male partner in prospering the earth and realizing an empowerment. With the collaboration between the two, life can go on and go straight, society can develop and the banner of justice and goodness will fly. Islam has taken care of women's civil rights as a whole, preserving their worthiness in carrying out their duties, conducting various transactions such as buying and selling, mortgaging, giving, willing, and several other forms of transactions. Islam also safeguards women's individual property rights more perfectly than teachings other than Islam. Islam also recognizes its full and independent authority in managing its assets and possessions without interference from anyone who might seize his property and ownership rights without his permission and permission even if the person is his husband. Islam has made it easier for women to become career women specifically in their behavior, business management and work. He can independently invest and produce, sell and buy, give and rent or give alms and other forms of sharia muamalah with the principles of freedom, independence of business without any intervention from outside parties.